Left Profunda Femoral Artery Pseudoaneurysm After Revision Total Hip Arthroplasty - Steven Baker, MD; Mary Kathryn Huddleston, MD; Tyler M. Goodwin, MD; Ryan Voskuil, MD; Case Sanders, MD (Arthroplasty Today, 2020)
We present a case report of an 84-year-old male who presented with a profunda femoris artery (PFA) pseudoaneurysm 8 years after the index revision total hip arthroplasty procedure. Failure of revision hardware and subsequent migration of implants led to damage of the PFA and pseudoaneurysm formation. The patient was hemodynamically unstable on presentation and required emergent endovascular intervention. Once medically stabilized, the patient underwent extensive debridement of the aneurysm and hematoma bed and broken hardware was removed to prevent further complications. At 6-month follow-up, the patient was able to mobilize independently and had returned to all prior levels of activities of daily living. We discuss the vascular anatomy of the hip, the paucity of literature on PFA pseudoaneurysm, as well as the likely etiology of total hip arthroplasty failures.